Do We Need to Choose Between Theory and Practice? On the Place of Logos and Praxis in Philosophy as a Way of Life - Marta Faustino (Eidos. A Journal for Philosophy of Culture)
The distinction between theory and practice, as well as their specific role, function, and relevance within philosophy is at the core of most metaphilosophical discussions of philosophy as a way of life (PWL). At the same time, Hadot’s emphasis on the practical dimension of ancient philosophy and its alleged privilege of practice over theory is one of the most polemic and controversial aspects of his account of PWL. In this paper I will discuss three alternative ways of interpreting Hadot’s characterization of PWL and the roles and functions of theory and practice in his account: John Cooper’s, Miranda Vilchi’s and Matthew Sharpe’s. After critically evaluating each one of these readings, I will present my own view on the matter and conclude with some reflections on the relevance (or irrelevance) of maintaining the opposition between theory and practice in our account of PWL.